Every crisis has a silver lining? Unravelling the pro-cyclical pattern of health inequalities by income - Max Coveney; Pilar Garcia-Gomez; Eddy van Doorslaer; Tom van Ourti (Tinbergen Institute, 2018)
It is well known that income and health are positively associated. Much less is known about the strength of this association in times of growth and recession. We develop a novel decomposition method that focuses on isolating the roles played by government transfers versus market transfers on changes in income-related health inequality (IRHI) in Europe. Using European Union Survey of Income and Living Conditions (EU-SILC) panel data for 7 EU countries from 2004 to 2013, we decompose the changes in IRHI while focusing on possible effects of the 2008 financial crisis. We find that such inequalities rise in good economic times and fall in bad economic times. This pattern can largely be explained by the relative stickiness of old age pension benefits compared to the market incomes of younger groups. Austerity measures are associated with a weakening of the IRHI reducing effect of government transfers.
Keywords: D30; D63; I14; I15; 330; Crisis; inequalities; health; income; decomposition